Analisis Pengetahuan Dengan Penilaian Kesiapan Perawat Pada Situasi Krisis Pasien Anak di IGD RSUD dr. Abdul Moeloek Provinsi Lampung Tahun 2025 - Velda, Ines Livia; Novikasari, Linawati; Setiawati; Wardiyah, Aryanti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Background: To handle the crisis conditions of pediatric patients, knowledge is needed with the assessment of nurse readiness and special skills in the ER, one of which is by understanding preparedness. Based on the recapitulation of the number of visits by pediatric patients in the ER of Dr. H. Abdul Moeloek Hospital, Lampung Province in 2023 was 35,683 and in 2024 was 25,341. The number of deaths in pediatric patients in 2024 was 164. The number of deaths of pediatric patients increases every year, if nurses on duty in the ER handle the crisis situations of pediatric patients properly, the number of deaths can decrease. Objective: To analyze the relationship between knowledge and nurse readiness in crisis situations of pediatric patients in the ER of Dr. H. Abdul Moeloek Hospital, Lampung Province. Method: The type of research used is quantitative descriptive analysis. The population in this study were all nurses who worked in the Emergency Room of Dr. H. Abdul Moeloek Hospital, Lampung Province, starting from January 25 to May 14, 2025, totaling 34 people. The sampling technique used in this study was total sampling. Results: Based on the results of statistical tests, the p-value data was obtained at 0.116 or p-value <0.05, which means that there is no statistically significant relationship between the level of knowledge and attitudes of nurses in dealing with crisis situations of pediatric patients in the Emergency Room of Dr. H. Abdul Moeloek Hospital, Lampung Province in 2025. Conclusion: It is hoped that the results of this study can add references for other students who want to conduct further research on emergency nursing in pediatric patients.